Students Awareness towards Traditional Cultural Dances in Sarawak, Malaysia - Ahmad R. Albattat; Irna Darini Amir; Nur Shuhada Nik Muhammad (Almatourism, 2016)
Malaysia has many ethnic groups, and each ethnic group has own custom and tradition that most Malaysians are not aware, especially traditional dances. Among the Malaysian states, Sabah and Sarawak, situated in the Borneo Island have the most diverse ethnic groups in Sarawak. It has more than 30 ethnic groups. Each of the ethnic groups has its own language, cultures and lifestyle. In this regards, this research focuses on the main ethnic groups of Sarawak which are Orang Ulu, Malays, Melanau, Bidayuh, Chinese and Ibans. The aim of this study is to investigate the level of awareness among the Management and Science University (MSU) students regarding their level of awareness and knowledge about traditional dances of Sarawak. The data were gathered by distributing questionnaires among MSU students. The data were then analysed using SPSS system version 18.0. Results concluded that, most of MSU students have limited knowledge about Sarawak traditional dances. Interests, internet, performing arts clubs and family background are the independent variable factors to learn and gain knowledge about Sarawak traditional dances. The level of awareness among MSU students towards Sarawak traditional dances can be enhanced through events and special occasions to increase level of awareness towards Sarawak cultures. The government plays a major role in introducing Sarawak cultures to the whole of Malaysia. Future studies could focus on factors that influence the level of awareness towards Sarawak traditional dances, and the contribution of Sarawak’s traditional dances to Malaysia’s cultural and heritage tourism.